2006
DOI: 10.2340/00015555-0093
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Diseases and Vitamin D Receptor Apa-I Polymorphism are Associated with Vitiligo in a Small Inbred Romanian Community

Abstract: Vitiligo has been associated with the host's genetic profile, metabolic abnormality and immunostatus. The purpose of this study was to investigate the association of vitiligo with autoimmune diseases for 31 out of 39 subjects with vitiligo and their first-degree relatives living in a small Caucasian inbred rural community. They were compared with healthy individuals. A 2.28% prevalence of vitiligo was calculated and the presence of consanguine marriages (72.3%) was noted for this community. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 34 publications
5
39
1
9
Order By: Relevance
“…As our study was performed in Toronto and the other in India, dietary and social differences between the two populations might have affected the results. The most likely confounding factor, however, is sun exposure, as it can stimulate the proliferation of melanocytes and affect the production of vitamin D, both of which can impact vitiligo [1,34]. An attempt was made to compensate for this by starting the study in May, but some participants were recruited late in the summer, and completed the 12 week study in November, thus experiencing substantial decreasing intensity of sun exposure over the last few months of their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our study was performed in Toronto and the other in India, dietary and social differences between the two populations might have affected the results. The most likely confounding factor, however, is sun exposure, as it can stimulate the proliferation of melanocytes and affect the production of vitamin D, both of which can impact vitiligo [1,34]. An attempt was made to compensate for this by starting the study in May, but some participants were recruited late in the summer, and completed the 12 week study in November, thus experiencing substantial decreasing intensity of sun exposure over the last few months of their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Because the study was open labeled, not controlled, and not randomized, it is quite likely that some of the demonstrated benefit may be due to a placebo effect. However, this is unlikely that all of the results we report can be accounted for by spontaneous repigmentation of vitiligo because these are generally considered clinically insignificant and cosmetically undetectable [34,43]. …”
Section: Limitationsmentioning
confidence: 99%
“…The mentioned study investigated 31 patients with vitiligo in a Romanian rural community which has a high rate of consanguine marriages reaching 72.3% [17]. It has always been expected that genetic patterns could be easily detected in such isolated populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these polymorphisms are associated with various diseases including psoriasis, diabetes mellitus and cancers [10,11,12,13,14,15,16]. Up to date, there is only one study showing that the Apa I polymorphism of the VDR gene is associated with vitiligo and might play a role in the etiopathogenesis of the disease [17]. Therefore, in this study, we aimed to investigate the association between VDR gene polymorphisms ( Bsm I, Apa I, Taq I, Fok I and Cdx2) and susceptibility to vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…According to the convergence theory various factors like autoimmunity, accumulation of melanocyte toxic chemicals, genetic predisposition and defective free radical clearance lead to the development of vitiliginous skin. 17 The serum vitamin D levels are lower in vitiligo patients as compared to non vitiligo patients. In vitro studies have shown that murine B-16 melanoma cells when treated with vitamin D3 exhibit an increase in tyrosinase activity and melanogenesis.…”
Section: Vitamin D Uses In Dermatological Conditionsmentioning
confidence: 99%